Islamic Historiography in North Sumatera: Analysis of Trends in Thesis Writing Themes at the History of Islamic Civilization Study Program 2020-2022 - Nabila Yasmin; M. Nasihudin Ali (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
This research examines the trend of thesis writing themes among History of Islamic Civilization students, Faculty of Social Sciences, in 2020-2022. The problems raised are the trending themes and their contributions to the development of Islamic historiography in North Sumatra. Therefore, this research aims to detail the trending thesis writing themes among students of the History of Islamic Civilization study program, Faculty of Social Sciences 2020-2022, and explain their contribution to the development of Islamic historiography in North Sumatra. The results show that the research themes selected are cultural history, archeology, biography, museums, architecture, education, political, intellectual, organization, art, and demographic histories. Furthermore, the most dominant theme is historical heritage and preservation efforts included in the scope of the archeology discipline, followed by traditions and culture in cultural history. The next themes are architecture, museums, literature, and biography, as well as political, intellectual, educational, organization, social, art, branding, and demographic histories. These themes have indirectly added to the references of Islamic historiography, particularly in local history research.